Learner autonomy development in the internet-environment - L K Raitskaya (Peoples' Friendship University of Russia (RUDN University), 2009)
The article analyses the notion 'learner autonomy' relating to the Internet as an educational information environment. The author considers ways and challenges for autonomy development at the time of educational paradigm change.